The Role of Forkhead Box Family in Bone Metabolism and Diseases - Xu, Jianxiang; Wang, Kanbin; Zhang, Zengjie; Xue, Deting; Li, Weixu; Pan, Zhijun (Frontiers in Pharmacology, 2022)
Forkhead box (Fox) family, an evolutionarily conserved family of transcription factors carrying the “Forkhead” motif, plays an indispensable role in human health and disease. Fox family genes are involved in cell differentiation, proliferation and apoptosis, embryonic development, aging, glucose and lipid metabolism, and immune regulation. The regulatory role of the Fox family in the context of bone metabolism and orthopedic diseases is an emerging research hotspot. In this review, we highlight the major molecular mechanisms underlying the regulatory role of Fox factors in bone metabolism, bone development, bone homeostasis, and bone diseases associated with inhibition or upregulation of Fox factors. In addition, we discuss the emerging evidence in the realm of Fox factor-based therapeutics.